Comment on “On the Use of the Term ‘Evapotranspiration’” by Miralles et al. (2020) - Sate Ahmad; Jennifer McElwain; Richard Nair; Laurence Gill (Water Resources Research)
Abstract In their 2020 commentary, Miralles et al. suggest reconsidering the use of the term “evapotranspiration” in favor of retaining the traditional term “evaporation” to refer to the vaporization of water from all surfaces, including plants. Their critique is based on four points: (a) historical controversy, (b) perceived redundancy, (c) aggregation of multiple processes leading to complexity, and (d) inconsistency in term usage. While we agree that there is value in improving contextual clarity, particularly regarding interception loss, we maintain that, given that globally, transpiration accounts for the majority (∼60–65%) of terrestrial water flux to the atmosphere, the use of the term “evapotranspiration” remains justified and has benefits depending on the specific context. The term effectively communicates complex ecohydrological processes by integrating both water transfer mechanisms and biotic processes. It is instrumental in fostering multidisciplinary collaboration and continues to be relevant across various scientific fields. Highlighting the strengths of using the term “evapotranspiration”, we propose that instead of abandoning it, efforts should be directed toward refining definitions within the context of their use to ensure clarity.